2014
DOI: 10.1002/ente.201402031
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation of an Iron Oxide‐Based Anode for Stable, High‐Capacity Lithium‐Ion Batteries of Porous Carbon–Fe3O4/Li[Ni0.59Co0.16Mn0.25]O2

Abstract: The lithium storage capacity of an iron oxide-based anode of porous carbon–Fe3O4 (i.e., PC–Fe3O4) was investigated by varying the initial current and mass density of the electrode to achieve a good utilization coefficient of the oxide. It was confirmed that these factors largely affected the capacity of PC–Fe3O4 and a certain mass density of the electrode was key to achieve a high area capacity (mAhcm-2). Moreover, the chemical and electrochemical lithiation of PC–Fe3O4 were related to the lithiation time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…It is interesting to note that, both magnetite and maghemite phases exhibit very similar XRD patterns and, therefore, careful analysis must be performed to distinguish between the phases. Recently, Ming et al [ 356 ] [ 352 ] Ji et al [ 353 ] fi rst demonstrated the performance of the Fe 3 O 4 -graphene composite as a conversion anode with layered type LiNi 1/3 Mn 1/3 Co 1/3 O 2 as the cathode.…”
Section: Fe 3 Omentioning
confidence: 99%
“…It is interesting to note that, both magnetite and maghemite phases exhibit very similar XRD patterns and, therefore, careful analysis must be performed to distinguish between the phases. Recently, Ming et al [ 356 ] [ 352 ] Ji et al [ 353 ] fi rst demonstrated the performance of the Fe 3 O 4 -graphene composite as a conversion anode with layered type LiNi 1/3 Mn 1/3 Co 1/3 O 2 as the cathode.…”
Section: Fe 3 Omentioning
confidence: 99%
“…In any case, the above results represent a significant improvement of the overall performances initially reported for “lithium–iron” cells with pre‐lithiated α‐Fe 2 O 3 , LiFePO 4 , PVdF and 1 m LiPF 6 . Such a system was limited by a 50 % loss of its capacity in 190 cycles at rates of less than 1C, unspecified round‐trip inefficiencies and an average output voltage of only approximately 2.2 V. Nonetheless, previous systematic studies of the chemical and electrochemical lithiation of iron oxide have also contributed to the development of Fe 3 O 4 /Li[Ni 0.59 Co 0.16 Mn 0.25 ]O 2 batteries with a higher operation voltage and a longer cycle life.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, the above results represent as ignificant improvement of the overall performances initially reported for "lithium-iron" cells [93] with pre-lithiated a-Fe 2 O 3 ,L iFePO 4 ,P VdF and 1 m LiPF 6 .S uch as ystem was limitedb ya50 %l oss of its capacityi n1 90 cycles at rates of less than 1C, unspecified round-trip inefficiencies and an average output voltage of only approximately 2.2 V. Nonetheless, previouss ystematic studies of the chemical and electrochemical lithiation of iron oxide [94] have also contributed to the development of Overall, our Li-rich electrodes based on Fe nanoparticles embedded in Li 2 Od emonstrate an alternative concept to overcome effectively the main drawbacks of iron oxide utilization in LIBs. Most likely, this could also be appliedt os imilarc onversion-type anode materials throught he general approachd evised here.…”
Section: Galvanostatic Tests Of Full Cellsmentioning
confidence: 99%
“…In contrast, the SnO 2 -C anode is more stable and cannot be easily inactivated because of the conversion/ alloying mechanism. [27] We find that 100%, 98.4% 94.4%, 91%, 86.6%, 82.2%, 80%, and 77.2% of the initial capacity can be preserved under the C of rates 0.1, 0.2, 0.5, 1, 2, 3, 4, and 5C, respectively (Figure 7d; Figure S15a, Supporting Information).…”
Section: High Performance Lithium-ion Battery Applicationsmentioning
confidence: 92%